Annual reproductive phenology of the coprophagous beetle Dichotomius satanas (Coleoptera: Scarabaeidae, Scarabaeinae) of the cloud forest in eastern Mexico. Issue 2 (8th April 2021) - Barretto, Julliana; Cruz, Magdalena; Escobar, Federico
Abstract: Reproductive phenology of organisms is modulated by biotic and abiotic factors, with direct effects on the demography. This study describes the annual reproductive phenology of Dichotomius satanas (Harold, 1867) (Coleoptera: Scarabaeidae, Scarabaeinae) of the cloud forest in eastern Mexico, through the morphological changes in the reproductive systems of individuals and their relationship with climatic conditions. Three stages of sexual maturity were recognised as occurring throughout the year: immature, maturing, and mature – with a higher occurrence of immature individuals. Abundance of immature and maturing females was explained by minimum temperature, but none of the environmental variables considered was related to mature females. Abundance of immature and maturing males was related to precipitation, while abundance of mature males was related to minimum temperature and precipitation. The phenology of D. satanas was markedly seasonal with a single peak of abundance corresponding to the reproductive period during the warm and rainy season, thus indicating a univoltine pattern of reproduction. Immature females were recorded before immature males, and no synchrony was observed between the maturing and mature males and females. We provide information pertaining to the reproductive biology of coprophagous beetles and highlight the importance of reproductive phenology as a tool with which to understand future environmental scenarios.